Analysis of general and specific combining abilities of popcorn populations, including selfed parents - Viana, José Marcelo Soriano; Matta, Frederico de Pina (Genetics and Molecular Biology, 2003)
Estimation of general and specific combining ability effects in a diallel analysis of cross-pollinating populations, including the selfed parents, is presented in this work. The restrictions considered satisfy the parametric values of the GCA and SCA effects. The method is extended to self-pollinating populations (suitable for other species, without the selfed parents). The analysis of changes in population means due to inbreeding (sensitivity to inbreeding) also permits to assess the predominant direction of dominance deviations and the relative genetic variability in each parent population. The methodology was used to select popcorn populations for intra- and inter-population breeding programs and for hybrid production, developed at the Federal University of Viçosa, MG, Brazil. Two yellow pearl grain popcorn populations were selected.
Keywords: Diallele cross; Combining ability; Inbreeding depression; Popcorn breeding